Evaluation of the Production Performances of an Endangered Local Poultry Breed, the Famennoise - Moula, N.; Antoine-Moussiaux, N.; Farnir, F.; Leroy, P. (International Journal of Poultry Science, 2009)
The Famennoise is a Belgian poultry breed which is greatly endangered. Like most of the local breeds in this situation, the Famennoise remains largely unknown and is representative of the continuous loss of genetic diversity that is threatening the future of animal production. From preliminary results, egg production traits in this breed showed valuable economic assets. The present study is, thus, aimed at assessing its production performances with the prospect that it might be conserved for future valorization. Egg production as well as growth traits were estimated. Both aspects showed exploitable performances. In absence of past selection for these traits, eggs presented a mean weight of 55.43 ± 3.03 g, so being in the middle class of marketable eggs, a yolk to albumen ratio of 50.7± 5.02 %, an eggshell resistance (maximal force of breakage of 36.03± 3.3 N) equal to commercial strains and superior to already valorized local breeds. In broilers, a mean weight 980.67±16.62 g was reached at 8 weeks, 1815.90 ± 36.55 g at week 12 and 2191.90± 48.31 g at week 15. The Famennoise is, therefore, suggested for use as a dual-purpose breed with a good potential of selection for both productions. It could further serve in crosses for improvement of commercial strains. In conclusion, it appears to be highly urgent to screen endangered local poultry breeds for economically exploitable traits which would motivate conservation programs of biodiversity, before this extraordinary scientific and economic potential get irremediably lost.